Manejo de residuos sólidos y bienestar social en habitantes del Asentamiento Humano Masusa. Punchana, Maynas. 2024 - Pinedo Ramirez, Priscila Naydu (2025)
This research work was developed in the Masusa human settlement in 2024. Its objective was to determine the relationship between solid waste management and social well-being in the inhabitants of said human settlement, in 2024. The research, due to its approach, is quantitative, due to data planning it is prospective and due to its level of research it is relational and its research design is non-experimental. The research had the participation of 68 residents, who were present during the application of the data collection instrument. The survey technique was used and two questionnaires were applied, each with 10 questions, which had previously been validated and subjected to reliability tests. The main results were: Variability was found in the responses on solid waste management in the Masusa human settlement, as well as variability in the responses on solid waste management, according to the level of instruction, being the educational level, Variability was identified in the responses on social well-being of the inhabitants of the Masusa human settlement, determining that the low social well-being is more accentuated in the female population (64.5%) and in people with secondary education (62.7%), It was identified that the relationship between solid waste management and social well-being in the Masusa human settlement presents a moderately intense positive association (Gamma = 0.315), although not statistically significant.